Real-time marketing & PR how to instantly engage your market, connect with customers, and create products that grow your business now - Scott, David Meerman (John Wiley & Sons, 2011)
Wake up, it & rsquo;s revolution time!Gone are the days when you could plan out your marketing and public relations programs well in advance and release them on your timetable. It & rsquo;s a real-time world now, and if you & rsquo;re not engaged, then you & rsquo;re on your way to marketplace irrelevance. & ldquo;Real time & rdquo; means news breaks over minutes, not days. It means ideas percolate, then suddenly and unpredictably go viral to a global audience. It & rsquo;s when companies develop (or refine) products or services instantly, based on feedback from customers or events in the marketplace. And i.
Includes bibliographical references and index. - Print version record
Keywords: Internet marketing; Public relations; Public Relations; Marketing sur Internet; Relations publiques; public relations